Microbial hallmarks of the respiratory tract in lung cancer: a meta-analysis - Zhu, Bin; McHale, Stephanie S.; Van Scoyk, Michelle; Riddick, Gregory; Wu, Pei-Ying; Chou, Chu-Fang; Tossas, Katherine Y.; Chen, Ching-Yi; Winn, Robert A. (Frontiers in Microbiomes, 2025)
IntroductionLung cancer is a leading cause of cancer-related deaths and has been associated with the microbiota of the human respiratory tract. However, the optimal sample type for studying the role of microbiota in lung cancer and the microbial hallmarks of lung cancer patients remain unclear. MethodsIn this study, we downloaded 16S rRNA sequencing data of 1,105 high-quality samples from 13 BioProjects, including lung tissues, bronchoalveolar lavage (BAL) fluids, and saliva, and performed a meta-analysis. ResultsOur results revealed that the BAL microbiota, dominated by taxa such as Sphingomonas and Pseudomonas, which are not typically abundant in the oral microbiota, served as hallmarks of individuals without lung cancer. In contrast, BAL samples from lung cancer patients showed higher relative abundances of oral-associated taxa, e.g., Streptococcus and Prevotella, with increased rates of dominance by these taxa in the BAL microbiota of lung cancer patients. Additionally, beta diversity analysis revealed significant compositional differences between the BAL microbiota of healthy individuals and those with lung cancer. Furthermore, while compositional differences were observed in the oral microbiota between healthy participants and lung cancer patients, as well as between microbiota from lung tumors and normal adjacent tissues, these differences were less pronounced than those observed in the BAL samples between healthy individuals and lung cancer patients. Cross-site correlations indicated limited associations between the relative abundances of taxa in the oral, BAL, and lung tissue microbiota, implying that differences in lower respiratory microbiota may not be directly driven by upper respiratory tract microbiota. DiscussionThese findings highlight distinct microbial patterns linked to lung cancer in the respiratory tract. More pronounced differences were observed in the BAL microbiota between healthy individuals and lung cancer patients, with the predominance of taxa, typically not abundant in the oral microbiota, serving as hallmarks of health.